Free-living nematode assemblages in the rhizosphere of watermelon plants in Nigeria: a baseline study - Bello, T.T.; Coyne, Danny L.; Fourie, H. (Brill, 2019)
Watermelon is increasingly produced and consumed in Nigeria and sub-Saharan Africa. However, limited information exists regarding nematode pests and beneficial/free-living nematodes associated with the crop. The present study recorded the abundance and diversity of free-living nematodes from 50 watermelon fields across south-west Nigeria during 2016/2017. Of the 30 genera identified from soil samples, Cephalobus, followed by Rhabditis, Aphelenchus and Aporcelaimus, were predominant. Variation in nematode community structures across the 50 fields was apparent for mean maturity indices, metabolic footprints, feeding-type composition and coloniser-persister (c-p) structure. Faunal analyses characterised 52% of the fields as having stable and enriched soil food webs, which is beneficial for crop production. Significant correlations were apparent between some nematode genera and selected soil properties, and rainfall. This study provides the first information of free-living nematodes associated with watermelon from sub-Saharan Africa, offering novel and baseline information on their abundance and diversity in south-west Nigeria.